Pengelolaan Limbah Organik Melalui Budidaya Maggot - I Made Pasek Amerta Bawa; Putu Shera Samantha; Devy Anggun Maheswari; Pande Made Wahyu Darma Putra (WICAKSANA: Jurnal Lingkungan dan Pembangunan, 2025)
This research aims to explore the effectiveness of maggot cultivation, especially Black Soldier Fly (BSF) larvae, in managing organic waste. The background to the problem includes the problem of organic waste management in Indonesia which still relies on conventional methods, such as landfills and incineration, which have negative impacts on the environment. The method used in this research is a literature study and data analysis from previous research regarding the potential and effectiveness of maggots in processing organic waste. The research results show that maggot cultivation has the ability to reduce the volume of organic waste by up to 60-80% in a short time and produce useful by-products, such as organic fertilizer and alternative animal feed. Apart from that, the social and economic potential of maggot cultivation provides great opportunities for the community, such as job creation and development of local entrepreneurship.